Evaluation of silica aerogel-reinforced polyurethane foams for footwear applications - Yang, Guang (2019)
In this work, a simple way to create a nanocellular structure within polyurethane (PU) foam was developed by the incorporation of silica aerogels, and the resultant foams were evaluated for footwear applications. To protect the brittle aerogels from breakage, the softness of PU foams was first tailored by changing the ratio of glycerol and polypropylene glycol. Different amounts of silica aerogels (0–15 wt%) were then loaded into a selected PU foam and analyzed in terms of compressive mechanical properties, shock attenuation performance, and thermal insulation. After incorporation of the aerogels, the compressive modulus, the compressive stress, and the deformation recovery of the foams improved, while the excellent flexibility was preserved. For simulated gait experiments, the shock attenuation capability of the foams was shown to increase with an increase in the aerogel content. These findings can probably be attributed to the improved elasticity of the solid phase and the changed morphology of the gaseous phase as observed from the SEM images. Moreover, the thermal insulation of the developed foams was also investigated, showing an increased trend with the aerogel content.